Optimization of Parameters for the Production of Ergot-Alkaloids by Claviceps purpurea PC-5 - Samdani, G.; Mahato, P.C.; Singh, S.P.; Rathor, Nalinin (Asian Journal of Chemistry, 2010)
The optimum culture conditions i.e., pH, temperature and incubationperiod have been studied for Claviceps purpurea PC-5. Ithas been found that activity of Claviceps purpurea PC-5 is maximumwhen 30% sucrose solution is allowed to ferment for 12 daysat 24°C temperature by maintaining the pH value of the medium at5.2.